COMPARISON OF BENIGN AND MALIGNANT BREAST DISEASE-RISK FACTORS AND FREQUENCIES IN SAMPLES REFERRED TO PATHOLOGY LABORATORY OF AHWAZ UNIVERSITY OF MEDICAL SCIENCES FROM 2006 TO 2017: Life Science-Surgery - RASHIDI, IRAN; KAVEH, PEYMAN; KIANIZADE, FATEMEH; REZASOLTANI, MAHSA; MOHAMMAD EGHBALNEJAD MOFRAD, AMIR; SAFARI KAHYESH, PARDIS; ALI KAVEH (International Journal of Life Science and Pharma Research, 2019)
Breast cancer is the most common malignancy in women contributing to about 18% of all cancers worldwide. There are many well-known risk factors for breast cancer, and identifying these risk factors will help to reduce the mortality rate. This study is aimed to compare risk factors and the frequencies in women with benign and malignant breast tumor. This case-control study, was done with 60 women with benign breast tumors as controls and 60 women with malignant breast tumors as case They were randomly selected and checklist was made. Based on the information in the forms of pathology or from medical records or patient contact, data was completed. Data analysis was conducted using SPSS-16 statistical software. The results showed that the mean age at diagnosis (p_value=0.033), the frequency of positive family history of cancer (p_value=0.028) and the mean age at menarche (p_value=0.01) in the two groups was statistically significant difference. However, the frequency of having an abortion (p_value=0.391), the mean age of first child birth (p_value=0.641), the mean months of breastfeeding (p_value=0.281) and the frequency of having a perfect pregnancy (p_value=0.58) did not show significant difference between the two groups. The mean age at diagnosis and the frequency of positive family history of tumors in the case group, and the mean age of menarche in the control group is higher implication